Publisher Correction: Structural and chemical biology of deacetylases for carbohydrates, proteins, small molecules and histones - Marco Bürger (Nature Portfolio, 2019)
In the original published version of the article, the protein name for the carbohydrate deacetylase in Geobacillus stearothermophilus was missing from Table 1. The protein name, Axe2 (corresponding to PDB code 3W7V), should have appeared immediately following the species name. In addition, a space was inadvertently omitted between Xanthomonas campestris and ACDase in Table 1. The errors have been corrected in the HTML and PDF versions.